2023
DOI: 10.3390/cells12091324
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte–Glioblastoma Cell Interaction: A Key Target to Prevent Glioblastoma Progression

Abstract: Multiple biological processes rely on direct intercellular interactions to regulate cell proliferation and migration in embryonic development and cancer processes. Tumor development and growth depends on close interactions between cancer cells and cells in the tumor microenvironment. During embryonic development, morphogenetic signals and direct cell contacts control cell proliferation, polarity, and morphogenesis. Cancer cells communicate with cells in the tumor niche through molecular signals and intercellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…We have demonstrated that the principal target cell of GBM during vascular co-option is the pericyte [7,11], which constitutes the primary cell type in the normal brain perivascular space. Then, cell-to-cell contact between GBMcs and PCs, along with the subsequent activation of pro-tumoral cellular and molecular processes in PCs, is essential for GBM growth and progression (Figure 2) ( [7,11,12] and reviewed in [13]). Additionally, following primary vascular co-option after GBM initial singularity, the GBM is generated and will invade the surrounding parenchyma, with the subsequent alteration of the brain-blood barrier (BBB), allowing other cells such as tumor-associated macrophages (TAMs) to infiltrate perivascular spaces, as well as the activation of microglia in the tumor microenvironment (TME) [14,15].…”
Section: The Role Of Pericytes In Glioblastoma Multiforme Generation ...mentioning
confidence: 99%
See 4 more Smart Citations
“…We have demonstrated that the principal target cell of GBM during vascular co-option is the pericyte [7,11], which constitutes the primary cell type in the normal brain perivascular space. Then, cell-to-cell contact between GBMcs and PCs, along with the subsequent activation of pro-tumoral cellular and molecular processes in PCs, is essential for GBM growth and progression (Figure 2) ( [7,11,12] and reviewed in [13]). Additionally, following primary vascular co-option after GBM initial singularity, the GBM is generated and will invade the surrounding parenchyma, with the subsequent alteration of the brain-blood barrier (BBB), allowing other cells such as tumor-associated macrophages (TAMs) to infiltrate perivascular spaces, as well as the activation of microglia in the tumor microenvironment (TME) [14,15].…”
Section: The Role Of Pericytes In Glioblastoma Multiforme Generation ...mentioning
confidence: 99%
“…Glioblastoma cells create an immunosuppressive TME at the edges of the tumor, where they encounter normal brain parenchyma cells, protecting GBMcs from detection and elimination by the immune system. They can release immunoregulative factors and establish cellular interactions that suppress immune responses, allowing the tumor to evade detection and destruction by immune cells [11][12][13][14]. Communication between GBMcs and TME cells is achieved through exosome interchange, soluble factors such as cytokines, chemokines, matrix-remodeling enzymes, and growth factors.…”
Section: Cellular Immunity In Glioblastoma Multiformementioning
confidence: 99%
See 3 more Smart Citations